Administration and Evaluation of Technology Integration and Adaptation: A Basis for Training Policies and Redirection of Technology-Enabled Learning - Mary Ann B. Taduyo; Augusto K. Fabella (Journal of ICT, Design, Engineering and Technological Science, 2017)
This paper presents the exploratory investigation of faculty trainees' technology preparedness and capability matrix, technology adaptation and integration strategies, challenges, and motivations in facilitating blended courses. The study employed the Sequential Explanatory Research Design. A Technology Preparedness and Capability Matrix developed by the researcher was administered to the training attendees. A semi-structured interview, Focus Group Discussion, and content analysis were used to gather and analyze qualitative data. Based on the results of the Technology Capability Matrix, the faculty trainees are capable of AV technology, the web and internet-based technologies, computing and smartphone devices, social networks, educational technologies, virtual classroom, e-learning authoring tools, office productivity suites, and other components of the office suite. Thematic patterns such as knowledge creation, improved student learning, 21st-century skills, and teachers' web and social presence. Participants elicited their challenges in developing learning materials into an Outcomes-based resource and in moderating the online community in order to create a technology-enhanced learning environment. The researcher recommends considering redesigning the TEL priorities for training and development using other LMS. It is also recommended to conduct studies on the relevance and effectiveness of TEL training to the learning facilitators.